Developing Community-Based Halal Tourism through Digital Promotion: A Case Study of Taman Surga Rinjani, Sembalun, Lombok, Indonesia - Hasbiatun Hasbiatun; Habibul Umam Taqiuddin; Muhammad Yakub (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2023)
This study explores the development of community-based halal tourism through digital promotion at Taman Surga Rinjani, located in Sembalun, East Lombok, Indonesia. As part of Lombok’s emerging halal tourism initiatives, this destination demonstrates how local communities integrate Islamic values with creative economic practices to enhance both spirituality and livelihood. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation involving local tourism managers, community members, and visitors. The analysis, guided by the Miles and Huberman framework, revealed that Taman Surga Rinjani applies a dual promotion strategy combining offline methods—such as local festivals, brochures, and school visits—with online marketing through social media platforms including Facebook, Instagram, and TikTok. These strategies have significantly increased tourist visits, stimulated local entrepreneurship, and created new employment opportunities. Moreover, the tourism model reflects Islamic ethical principles of halalan tayyiban (permissible and good), amanah (trust), and ukhuwah islamiyah (social solidarity). Despite notable progress, challenges remain in terms of digital marketing capacity, partnership development, and limited institutional policy support. The study concludes that sustainable halal tourism requires continuous collaboration between government agencies, local communities, and digital innovators. This research contributes to the growing discourse on Islamic tourism by demonstrating how digital engagement and community participation can transform peripheral destinations into inclusive and ethically grounded tourism ecosystems.